The experience of ageing, spirituality, and health as a Muslim woman in Canada - Farooq, Zanab (Journal of religion, spirituality & aging, 2024)
How does spirituality relate to ageing for Muslim women? The purpose of this study was to better understand the experience and intersections of ageing, spirituality, and health for Muslim women in Canada. This better understanding would be beneficial for care providers who may be unaware of the needs of ageing Muslim women. Four Muslim women, each in their fifties, participated in a qualitative, semi-structured interview. Seven themes were identified to be most relevant: Faith, identity, spiritual wisdom, accommodation, self-care, perceived judgement, and reconnecting the Muslim community. Recommendations are made not only for care providers, but for Muslim women and for the Muslim community in general.